If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5(2x + -4) + 10 = 5x + 35 Reorder the terms: 5(-4 + 2x) + 10 = 5x + 35 (-4 * 5 + 2x * 5) + 10 = 5x + 35 (-20 + 10x) + 10 = 5x + 35 Reorder the terms: -20 + 10 + 10x = 5x + 35 Combine like terms: -20 + 10 = -10 -10 + 10x = 5x + 35 Reorder the terms: -10 + 10x = 35 + 5x Solving -10 + 10x = 35 + 5x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-5x' to each side of the equation. -10 + 10x + -5x = 35 + 5x + -5x Combine like terms: 10x + -5x = 5x -10 + 5x = 35 + 5x + -5x Combine like terms: 5x + -5x = 0 -10 + 5x = 35 + 0 -10 + 5x = 35 Add '10' to each side of the equation. -10 + 10 + 5x = 35 + 10 Combine like terms: -10 + 10 = 0 0 + 5x = 35 + 10 5x = 35 + 10 Combine like terms: 35 + 10 = 45 5x = 45 Divide each side by '5'. x = 9 Simplifying x = 9
| 5+2r=2r+6 | | 0.98(8)-1.04p=0.98(8+p) | | 3(2x-2)-9=-x+34 | | 7a-3=3+6n | | 30=5(x+2) | | 0.98(8)+1.04p=0.98(8+p) | | 3(2x-1)-3=48 | | 2(x-1)=-x+16 | | -x-9=3x+11 | | -x+47=4(x-2) | | -7x-3x+2=-8 | | 2x^2+4y^2-4x-24y+36=0 | | (2x-3)/7=(3x)/7-2x | | p^3-4p^2-p+4= | | 2.2q-3.9-2.8q=-1.6q-1.8 | | 4n=m(5-n) | | 3x^2-10x-28=0 | | -x^2+14x-57=0 | | -10=30 | | 64=2a+a^2+1 | | 2x^3+x^2-4x-3=0 | | x+4=2(.4x+1.3) | | 15x^3-43x^2+28-4=0 | | 0=60x-3x^2 | | 3x+71=44 | | 4-7f=25 | | 27-3e=18 | | 10+4d=-26 | | x(x-2)=(x+2) | | 5x-13=4(2x-5) | | 5b+6-6b+2= | | 9x^2-32=40 |